A new Amazonian species of Cryptocellus (Arachnida, Ricinulei), with descriptions of its integumental structures and all free-living life stages - Tourinho, Ana Lúcia; Lo-Man-Hung, Nancy França; Salvatierra, Lidianne (Zootaxa, 2014)
A new species of Cryptocellus Westwood, 1874 is described, based on males, females and all free-living immature stages. Cryptocellus muiraquitan sp. nov. from Juruti, Pará, Brazil, is a member of the foedus group of species and probably closely related to Cryptocellus icamiabas Tourinho & Azevedo, 2007, C. abaporu Bonaldo & Pinto-da-Rocha, 2003 and C. simonis Hansen & Sørensen, 1904. The new species is illustrated using stereomicroscopy and scanning electron microscopy. The large diversity of integumental structures of the new species is described and compared to that of previously studied species of Cryptocellus and Pseudocellus Platnick, 1980.